Near-inertial mixing in the central Arctic Ocean - Fer, Ilker (Journal of Physical Oceanography, 2018)
Observations were made in April 2007 of horizontal currents, hydrography, and shear microstructure in the upper 500 m from a drifting ice camp in the central Arctic Ocean. An approximately 4-day-long time series, collected about 10 days after a storm event, shows enhanced near-inertial oscillations in the first half of the measurement period with comparable upward- and downward-propagating energy. Rough estimates of wind work and near-inertial flux imply that the waves were likely generated by the previous storm. The near-inertial frequency band is associated with dominant clockwise rotation in time of the horizontal currents and enhanced dissipation rates of turbulent kinetic energy. The vertical profile of dissipation rate shows elevated values in the pycnocline between the relatively turbulent underice boundary layer and the deeper quiescent water column. Dissipation averaged in the pycnocline is near-inertially modulated, and its magnitude decays approximately at a rate implied by the reduction of energy over time. Observations suggest that near-inertial energy and internal wave–induced mixing play a significant role in vertical mixing in the Arctic Ocean. publishedVersion